Financial Performance Before And After Stock Split On The Indonesia Stock Exchange In 2018: Kinerja Keuangan Perusahaan Sebelum Dan Sesudah Stock Split Di Bursa Efek Indonesia Tahun 2018 - Hanifah, Azimah; Riyanti; Zulkarnain, Iskandar (Procedia of Social Sciences and Humanities, 2022)
This study discusses the company's activities on the Indonesia Stock Exchange that conduct a Stock Split. The purpose of this study was to analyze whether there were differences in financial performance before and after the company did a stock split. 12 companies carried out a stock split in 2018 that met the research criteria to be used as research samples. This study uses a comparative test or a test that compares the company's financial performance before and after the company conducts a stock split. The year the researcher chose was 2018. Using data from 2016 and 2017 for the year before the company did the stock split and 2019 and 2020 after the company did the stock split. Researchers used financial ratios, namely Current Ratio (DER), Return On Assets (ROA) and Debt to Equity Ratio (DER). The results showed that there were no differences in the company's financial performance before and after the company did a stock split.